Long-Term Results of Stenting in Patients with Hemodynamically Significant Lesions of the Left Main Coronary Artery - Olena V. Levchyshyna; Sergii V. Salo; Yevhenii V. Aksonov; Mykola S. Kyba (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To study the long-term results of stenting in patients with coronary artery disease with hemodynamically significant left main coronary artery (LMCA) stenoses.Materials and methods. The study included 67 patients (56 men, 11 women) with a mean age of 63 ± 2.1 years.Results. Among the 67 patients included in the study, 29 patients (43.3%) underwent percutaneous coronary inter-vention using a single-stent technique. These were patients with ostial LMCA lesions, lesions of the middle third of the LMCA and some patients with Medina 1.1.0; 1.0.1; 1.0.0; 0.1.0; 0.0.1 lesions of the distal part of the LMCA. The median follow-up was 2 years. Using a questionnaire, we managed to establish contact with 25 patients (86.2%). Among these, 1 patient (3.4%) died of non-cardiac causes and 7 patients (24.1%) had a recurrence of angina within 2 years. The causes of angina recurrence in 2 cases (6.9%) were restenosis in the stent with transition to the mouth of the side branch, which required repeated stenting of the LMCA with transition to the left circumflex artery. In 5 patients (17.2%), angina recur-rence was associated with progression of coronary atherosclerosis of another localization.Among 67 patients with LMCA stenting, the two-stent technique was used in 38 patients (56.7%). These were pa-tients with Medina 1.1.0; 1.0.1; 1.0.0; 0.1.0; 0.0.1 lesions of the distal part of the LMCA. The median follow-up was 2 years. Using a questionnaire, we managed to contact 35 patients (92.1%). Among these, 4 patients (10.5%) died, but only one of them due to cardiac causes (2.6%), and 3 patients (7.9%) had recurrent angina within 2 years, two of whom underwent stenting by the T and protrusion (TAP) technique and one by culotte. The first two patients underwent angioplasty of restenosis in stents using balloons with a therapeutic coating. In the last patient, stent recoil in the left circumflex artery mouth was observed due to severe calcification, so this patient underwent re-implantation of the stent system in the recoil zone.Conclusions. The problem of choosing a method of revascularization for patients with hemodynamically significant LMCA lesions remains controversial to this day, despite the wide range of evidence. Doctors should jointly decide on the choice of treatment methodology solely in the interests of the patient, taking into account all the factors that may affect the patient’s quality of life in the long term.